Development of information technology (IT) and communication system in shipping: new paradigm shift? / Norakmam Hussin - Hussin, Norakmam (2002)
As long as there are oceans and waterways, there will be ship plying and trade will continue to be moved by sea because it is arguably the cheapest form of transportation. Hence, it is not surprising that shipping is one of the biggest and most important economic activities in the world today. The shipping industry is in an era of change. With the advancement of the Information Technology which will believed either could inspires, intrigues or activates will always depend on the approach by parties to emerging technology. Therefore as the new millennium dawns, the shipping industry faces more challenges and opportunities in facing the supply and demand balances but the capability offered by advances in information technology will enable new thinking, new approaches and maybe will invite new players to enter the equation. The information technology will also change the way shipping information and data are being access, process, and transferred. The impact of the communication technology are not only limited to improvement ship-to-shore and ship-to-ship communication but also playing important role in shore-to-shore communication with other supporting industries involved in shipping such as insurance, legal, ship brokering, ship agencies, ports and others. Since her early ocean trade the business had been done in a very conservative ways, this paper will report the need to shift or paradigm shift in the industry in line with the latest technology. The exposure of the advantages address in the paper will help the industry to be more open minded and ready to shift to the new technology era.